An Investigation of the Impact of Concurrent Group Dynamic Assessment on EFL Learners’ Achievement of Phrasal Verbs at Productive Level - Moghadam, Fatemeh Sadat Alavi; Farahani, Fatemeh (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2020)
The present study aimed at investigating the impact of the concurrent group dynamic assessment on the learning of phrasal verbs at a productive level. The participants of the study were 30 EFL learners at an intermediate level of language proficiency. The participants’ productive knowledge of the phrasal verbs was measured before and after the treatment through a researcher-made test including 80 items. For the purpose of the study, paired and independent samples t-test were utilized. Results of statistical analyses indicated that concurrent group dynamic assessment was significantly effective in the achievement of phrasal verbs at a productive level. Moreover, it was found that no significant difference existed in the concurrent group dynamic assessment in terms of the achievement of phrasal verbs at a productive level.